Faktor-Faktor Yang Berhubungan Dengan Kejadian Anemia Pada Remaja Putri Di Sman 29 Kabupaten Tangerang: FACTORS RELATED TO THE INCIDENT OF ANEMIA IN ADOLESCENT GIRLS IN SMAN 29 TANGERANG DISTRICT - Rita Tri Wahyuningsih; Eka Bati Widyaningsih; Fitrya Ayu Anggraini (Indonesian Journal of Midwifery Scientific, 2024)
Background: According to the World Health Organization (WHO) the world prevalence of anemia in young women is around 53.7%, while in Tangerang Regency in 2018 it was 37.1%. One of the programs from the Ministry of Health to overcome anemia in young women is to run a program of giving blood-added tablets to young women with a target of 30%, but there are still young women who experience anemia. One of the factors that influence the occurrence of anemia is knowledge, adherence to taking iron tablets, rest patterns, menstrual patterns, and eating patterns. Objective: to find out the factors associated with the incidence of anemia in young women at SMAN 29 Tangerang Regency in 2023. Methodology: The research method is quantitative analytic research using a cross sectional research design. The sample in this study were 140 young women who had experienced menstruation at SMAN 29 Tangerang Regency using a purposive sampling technique. Data were analyzed using the Chi Square test. Results: There is a relationship between knowledge (p value=0.000), adherence to taking blood supplement tablets (p value=0.000), rest patterns (p value=0.000), menstrual patterns (p value=0.000) and eating patterns (p value=0.025) with the incidence of anemia in young women.